Pseudorange estimation algorithm combining code and carrier phase based on Gaussian sum particle filtering - LI Li-min1; GONG Wen-bin1; LIU Hui-jie1; YU Jin-pei1 (Tongxin xuebao)
According to the characteristic that code measurements yielded noisy but unambiguous pseudorange estimates and carrier phase measurements were almost noiseless but were affected by integer ambiguity,a novel Gaussian sum particle filter（GSPF） algorithm was proposed to combine the advantages of the two measurements.The theoretical analysis and simulation results show that the proposed algorithm is immune from cycle slips and produces smaller mean square errors.